Field notes contributed by Dennis Henrickson, February 26, 1982 - Henrickson, Denniset al (1982)
Field notes were contributed by Dennis Henrickson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed